Socioeconomic status and childhood mortality in North Carolina. - Nelson, M D (1992)
Children in families eligible to receive Aid to Families with Dependent Children (AFDC) were found to have substantially higher mortality rates than non-AFDC children. The disparity seems to be greater for Whites than for non-Whites. These results suggest the presence of social class differentials in access to and use of health care and related services and facilities, in exposure to environmental risks, and in knowledge of injury control measures.